2015
DOI: 10.1128/aem.02617-14
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Genomics of a Small-Colony Variant in a Pseudomonas chlororaphis 30-84 Biofilm

Abstract: The rhizosphere-colonizing bacterium Pseudomonas chlororaphis 30-84 is an effective biological control agent against take-all disease of wheat. In this study, we characterize a small-colony variant (SCV) isolated from a P. chlororaphis 30-84 biofilm. The SCV exhibited pleiotropic phenotypes, including small cell size, slow growth and motility, low levels of phenazine production, and increased biofilm formation and resistance to antimicrobials. To better understand the genetic alterations underlying these pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…This study, as well as those of others (Koh et al, 2007;Singh et al, 2009;Workentine et al, 2010;Cooper et al, 2014;Wang et al, 2015), have shown that the production of morphotypic variants is commonly associated with biofilm formation, where mutations are induced by stresses such as starvation and oxidative stress (Bjedov et al, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…This study, as well as those of others (Koh et al, 2007;Singh et al, 2009;Workentine et al, 2010;Cooper et al, 2014;Wang et al, 2015), have shown that the production of morphotypic variants is commonly associated with biofilm formation, where mutations are induced by stresses such as starvation and oxidative stress (Bjedov et al, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…SCV formation is also observed in P. aeruginosa strains (Coggan and Wolfgang, 2012;Drenkard and Ausubel, 2002) and Pc30-84 (Wang et al, 2015). These variants show modifications in the genes that increase the levels of c-di-GMP, consistent with a battery of phenotype changes focused on a loss of motility and but a gain of strong biofilm formation (Römling et al, 2013;Valentini and Filloux, 2016).…”
Section: Gacs-dependent But Rpos-independentmentioning
confidence: 72%
“…3. Gac/Rsm regulation was reported to act central role on biofilm formation in pathogenic P. aeruginosa isolates (Frangipani et al, 2014) and in Pc isolate 30-84 (Wang et al, 2015). To understand biofilm formation in PcO6, we have studied two of the processes involved, cell motility and extracellular matrix production.…”
Section: Root Colonization and Biofilm Formationmentioning
confidence: 99%
“…Therefore, the role of fusA, which codes for an elongation factor, in the initial protection against tobramycin can be understood in terms of its function in biofilm formation by Pseudomonas chlororaphis (31). The rplB gene codes for a 50S ribosome-associated L2 protein that is known to be involved in bactobolin resistance (32).…”
Section: Discussionmentioning
confidence: 99%